The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0100-204x2013000800020
|View full text |Cite
|
Sign up to set email alerts
|

Feeding rate and frequency on juvenile pompano growth

Abstract: -The objective of this work was to evaluate the ideal feeding rate and frequency for juvenile pompano (Trachinotus marginatus). Two experiments were carried out in a completely randomized design, with three replicates each. In experiment I, 25 fish (4.8±0.6 g and 6.48±0.01 cm) were stocked in 15 tanks (50 L) during 21 days and fed 4, 8, 12, 16, and 20% body weight per day. In experiment II, 20 fish (4.1±0.1 g and 6.6±0.1 cm) were stocked in 15 tanks (40 L) during 28 days and fed 2, 6, 8, and 10 times a day. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
(36 reference statements)
2
11
0
2
Order By: Relevance
“…On the other hand, some studies have shown that increased frequency may lead to a reduction in feed conversion. Cunha et al, () evaluated different frequencies (2, 6, 8 and 10 times a day) and obtained a lower feed conversion using higher feeding frequencies. Kasiri et al, () concluded that an increased feeding frequency resulted in greater food consumption and fish growth; however, inversely proportional, higher frequencies caused a poorer food conversion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, some studies have shown that increased frequency may lead to a reduction in feed conversion. Cunha et al, () evaluated different frequencies (2, 6, 8 and 10 times a day) and obtained a lower feed conversion using higher feeding frequencies. Kasiri et al, () concluded that an increased feeding frequency resulted in greater food consumption and fish growth; however, inversely proportional, higher frequencies caused a poorer food conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Defining food management should allow for the full manifestation of the species performance, the economic viability of the crop and its environmental sustainability, with a focus on effluent reduction (Cunha, Shei, Okamoto, Rodrigues, & Sampaio, ). Feeding frequency is a component of food management which defines how many times the food will be offered throughout the 24 hours of the day.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A utilização de dietas para peixes marinhos pode ser limitada pela ausência de informações sobre práticas adequadas de manejo alimentar (Ramos et al, 2012, Sanches et al, 2014. A determinação do protocolo alimentar contribui para reduzir o desperdício de ração e o lançamento de efluentes, elevando o retorno econômico dos cultivos (Cunha et al, 2013).…”
Section: Compensatory Growth and Food Deprivation In Common Snook Grounclassified